Observation of Cooper pairs in a mesoscopic two-dimensional Fermi gas - Holten, Marvin; Bayha, Luca; Subramanian, Keerthan; Brandstetter, Sandra; Heintze, Carl; Lunt, Philipp; Preiss, Philipp; Jochim, Selim (Nature, 2022)
The formation of strongly correlated fermion pairs is fundamental for the emergence of fermionic superfluidity and superconductivity1. For instance, Cooper pairs made of two electrons of opposite spin and momentum at the Fermi surface of the system are a key ingredient of Bardeen-Cooper-Schrieffer (BCS) theory—the microscopic explanation of the emergence of conventional superconductivity2. Understanding the mechanism behind pair formation is an ongoing challenge in the study of many strongly correlated fermionic systems3. Controllable many-body systems that host Cooper pairs would thus be desirable. Here we directly observe Cooper pairs in a mesoscopic two-dimensional Fermi gas. We apply an imaging scheme that enables us to extract the full in situ momentum distribution of a strongly interacting Fermi gas with single-particle and spin resolution4. Our ultracold gas enables us to freely tune between a completely non-interacting, unpaired system and weak attractions, where we find Cooper pair correlations at the Fermi surface. When increasing the attractive interactions even further, the pairs gradually turn into deeply bound molecules that break up the Fermi surface. Our mesoscopic system is closely related to the physics of nuclei, superconducting grains or quantum dots5-7. With the precise control over the interactions, particle number and potential landscape in our experiment, the observables we establish in this work provide an approach for answering longstanding questions concerning not only such mesoscopic systems but also their connection to the macroscopic world.